Assessment of Water Quality Parameters of Owala Dam - Adewale, Balogun Hassan; Olubanjo, Fawole Olatunde (Asian Journal of Advanced Research and Reports, 2025)
Water quality monitoring is crucial for managing freshwater resources as it provides valuable data for local action planning and decision-making. This study assessed the water quality of Owala Dam, Osun State, Nigeria. Water samples were collected monthly from three stations along the Oba-Ile River (Owala Dam) in Olorunda between 2021 and 2024, and analyzed in the laboratory following standard protocols. In-situ measurements included water temperature (mercury-in-glass thermometer, 0–110°C, 0.1°C intervals), pH (Mueel meter), and electrical conductivity (Lovibond meter). Dissolved oxygen (DO) was measured using Winkler’s method, while biochemical oxygen demand (BOD) was calculated via the five-day BOD test. Total dissolved solids (TDS) were determined through filtration and evaporation, sulphate by the turbidimetric method, and chloride using the APHA titration method with potassium dichromate and AgNO₃. Phosphate levels were determined colorimetrically using a spectrophotometer after treatment with ammonium molybdate and stannous chloride. Results showed a slight, statistically insignificant rise in temperature (25.85°C in 2021/2022 to 26.39°C in 2023/2024). pH remained within the acceptable range (6.5–8.5) set by the Nigerian Standard for Drinking Water Quality (NSDWQ) and WHO. TDS remained constant at ~0.57 mg/L. BOD decreased significantly (p = 0.016), while DO levels were high (~66 mg/L), exceeding WHO's minimum of 6 mg/L. Transparency declined significantly (p < 0.05). Electrical conductivity was stable (~0.34 ds/m), below the 1000 ds/m limit. Nitrate (~0.07 mg/L) and phosphate levels were consistently low, and chloride levels (~40 mg/L) were within safe limits. Except for DO, all parameters complied with WHO standards. Continuous monitoring is therefore recommended in this dam to ensure sustainable water resource management.